Comparative Analysis of Inflation Dynamics of Three African Countries: Ethiopia, Kenya and South Africa - DESA DABA FUFA (Ethiopian Journal of Science and Sustainable Development, 2020)
This paper examines a comparative view of the inflation dynamics in three African countries. The study used monthly data from January 2007 to April 2018. To achieve the objectives, the study was deployed varieties of econometric methods. The exploratory analysis reveals that inflation of the sampled countries exhibits similar trends over the long run. The Johansson Co-integration test result evince that inflation, oil price and exchange rate of Ethiopia and South Africa had a long run relationship. Exchange rates had significant positive effects on inflation dynamics of both countries while world oil price contributes positively in Ethiopia but negatively in South Africa. In the short run, inflation in Kenya was found to be a sign of Ethiopia’s inflation. Likewise, in South African inflation was an indicator of the inflation in Kenya whereas inflation in Kenya and Ethiopia could not predict inflation would occur in South Africa. Furthermore, the outcome of the impulse response function demonstrates that exchange rates and oil price shocks affected inflation dynamics of the sampled countries at different stages both directly and indirectly. In the short run, shocks to inflation have an interaction effect across the selected countries. The findings also report that world oil prices are not equally contributes for inflation dynamics in the sampled countries.